Cervical Extensor Muscles Play the Role on Malalignment of Cervical Spine: A Case Control Study With Surface Electromyography Assessment - Wang, Dian; Ding, Yi; Wu, Bingxuan; Si, Fangda; Yu, Fan; Xiao, Bowei; Liu, Baoge (Spine (Philadelphia, Pa. 1976), 2021)
A case control study. The aim of this study was to identify the potential impact of cervical spine malalignment on muscle parameters. Muscular factors are associated with cervical alignment. Nevertheless, only muscle dimensions or imaging changes have been evaluated, function of cervical muscles has scarcely been investigated. Thirty-four patients diagnosed as cervical spine degeneration associated with cervical malalignment and 32 control subjects were included in this case control study. Visual analogue scale (VAS) and the neck disability index (NDI) were used. The sagittal alignment parameters and cervical range of motion (ROM) were measured on cervical spine lateral radiographs, included C2-C7 lordosis, C2-C7 sagittal vertical axis (C2-C7 SVA), cervical gravity-sagittal vertical axis (CG-SVA), T1-Slope, and spinal canal angle (SCA). Surface electromyography (SEMG)-based flexion-relaxation ratio (FRR) was measured. The result showed VAS score of the neck significantly lower in controls (P<0.05), C2-C7 lordosis, C2-C7 SVA, CG-SVA, T1-Slope and ROM showed significantly different (P<0.001) between malalignment group and control group, FRR of splenius capitis (FRRSpl) and upper trapezius (FRRUTr) of the malalignment group were lower than in the control group, which correlated well with NDI (rSpl = -0.181 rUTr = -0.275), FRRSpl correlated well with VAS (rSpl = -0.177). FRRSpl correlated strongly with C2-C7 SVA (r = 0.30), CG-SVA (r = 0.32), T1-Slope (r = 0.17), ROM (r = 0.19), FRRUTr correlated with C2-C7 lordosis (r = -0.23), CG-SVA (r = 0.19), T1-Slope (r = 0.28), ROM (r = 0.23). Cervical malalignment patients had more tensional posterior cervical muscle and poor muscle functions. CG-SVA showed advantages in evaluating cervical malalignment.Level of Evidence: 3.